(untitled) (SCIENCE TIME JOURNAL, 2026)
In this article, politeness is considered an important part of speech etiquette in the Karakalpak and English languages. The research explains the lexical units which are used to express politeness and cultural interaction. In particular, addressing forms, expressions of apologies, requests, permission and gratitude are specifically highlighted. The results show that although linguistic strategies are used to express politeness in both languages, they differ from each other in terms of clarity and cultural characteristics.